(untitled) (Nigerian Journal of Cooperative Economics and Management, 2026)
This study examines the effect of corporate tax aggressiveness on the financial performance of listed non-financial firms in Nigeria. Using panel data spanning 2015 to 2023 across 40 firms listed on the Nigerian Exchange Group (NGX), the study employs the Effective Tax Rate (ETR) as the primary proxy for tax aggressiveness, supplemented by the Book-Tax Difference (BTD) as an alternative measure in robustness checks. Return on Assets (ROA) and Tobin’s Q serve as the primary dependent variables, operationalising accounting-based and market-based performance respectively. Fixed-effects regression is adopted following the Hausman specification test. Additional robustness checks employ the System Generalized Method of Moments (GMM) estimator to address potential endogeneity, quintile regression to explore heterogeneous effects across the performance distribution, and an alternative ETR proxy to test for measurement sensitivity. Findings confirm that tax aggressiveness exerts a statistically significant positive effect on ROA but a negative and significant effect on Tobin’s Q - a duality that persists robustly across all estimation strategies. These results suggest that while tax savings inflate reported earnings, capital markets discount firms perceived as tax aggressive owing to elevated regulatory and reputational risks, particularly in the post-Post-Finance Act environment. The study contributes to the sparse empirical literature on tax aggressiveness in sub-Saharan Africa and provides actionable guidance for corporate boards, investors, and regulators.